Polyphony of modern Ukrainian epic: tradition and reconstruction (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article deals with the analysis of polyphony in modern prose work. Intragenre possibilities of short story аs a small epic form and result of nongenre recations are examined in the investigation in works of «NeprOsti» by Taras Prokhaskо, «Osin' za shhokoyu» by Vasyl Slapchuk, «Voroshylovgrad» by Serhij Zhadan, «Anatomichnyj atlas. Vazhko buty zhaboyu» by Artem Chekh.
Keywords: polyphony; structure; novel; prose; poetics; tradition; deconstruction